(untitled) (Research, Society and Development, 2020)
The Law No. 11,947 of 2009 establishes that at least 30% of the resources allocated to the Brazilian School Feeding Program (PNAE as its acronym in Portuguese) must be used for the purchase of family farming products, which is important for students’ food security and as distribution channel for farmers. This paper aims to evaluate the impact of PNAE remuneration on the family farmers’ income in the municipality of Tupã-SP. To reach this end, 23 farmers who participated in the PNAE were interviewed and the data were worked through descriptive statistics, Pearson’s Linear Correlation and Monte Carlo Simulation. The results indicate that 39.1% of farmers sell between R 15,001.00 /year to R 20,000.00/year to PNAE and that the participation in the program can represent a growth of up to 60.45% in total income. Therefore, the information collected in this study can contribute to the decision of farmers to participate or not in the program, since the adhesion to PNAE can demand improvements in planning and production.